2013
DOI: 10.1177/0143831x13505119
|View full text |Cite
|
Sign up to set email alerts
|

Understanding nurses’ work: Exploring the links between changing work, labour relations, workload, stress, retention and recruitment

Abstract: This article enhances our understanding of nurses' work as they see it, in an exploration of the links between changing work, the labour relations climate, workload, stress, retention and recruitment. Conventionally separate bodies of literature on occupational health and safety, public sector industrial relations and human resource management informed the design and implementation of the study. Interviews with nurses revealed a high level of commitment but also indicated clear links between the labour relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 41 publications
0
25
0
4
Order By: Relevance
“…In other African contexts nurses document their actions including their advocacy actions to ensure patient safety [ 14 ]. However some studies in the Ghanaian and broader African contexts show that nurses are often overworked and may lack the energy and time to advocate for patients [ 13 , 15 , 16 ] due to insufficient staff numbers [ 17 ]. Poor remuneration and lack of resources at work [ 15 , 18 ] as well as their low level of participation in decision-making in the hospital [ 18 ] can also lead to frustration.…”
Section: Introductionmentioning
confidence: 99%
“…In other African contexts nurses document their actions including their advocacy actions to ensure patient safety [ 14 ]. However some studies in the Ghanaian and broader African contexts show that nurses are often overworked and may lack the energy and time to advocate for patients [ 13 , 15 , 16 ] due to insufficient staff numbers [ 17 ]. Poor remuneration and lack of resources at work [ 15 , 18 ] as well as their low level of participation in decision-making in the hospital [ 18 ] can also lead to frustration.…”
Section: Introductionmentioning
confidence: 99%
“…2 Another study carried out with Canadian public health workers showed a substantial increase in the workload due to a lack of structure and adequate working conditions, where the lack of human resources entails the need to take on external roles. 23 The data from this study reveals that the precariousness of the work culminates in the increase of the psychological load.…”
Section: Discussionmentioning
confidence: 69%
“…I interviewed 10 petroleum business leaders (Five each) from two organizations in NDPSI (Company A and B) situated in Oghara, Delta state of Nigeria. Hart and Warren (2015) noted that in a qualitative study, scholars may attain data saturation from a sample consisting of 10 participants. I ensured data saturation by interviewing participants until no new themes emerged.…”
Section: Study Population and Samplementioning
confidence: 99%
“…Yin (2014) affirmed that researchers use semistructured interviews to obtain individual perspectives and firsthand explanations of the topic under study. Hart & Warren (2015) asserted that researchers use open-ended questions to allow the participants to elaborate on the research topic and provide in-depth perceptions. Moreover, Rowley (2012) posited that a face-to-face interview setting allow researchers to obtain valuable responses by enhancing participant confidentiality.…”
Section: Data Collectionmentioning
confidence: 99%